Precis of inquiry under bounds. - Thorstad, David (Philosophical Studies, 2026)
The article focuses on developing a theory of bounded rationality that addresses how agents with limited cognitive abilities and costly inquiry processes can rationally form intentions, preferences, and beliefs. It contrasts the traditional Standard Picture of rationality, which emphasizes structural consistency, with bounded rationality’s process-focused, ecological, and heuristic-based approach. Central to the article is the reason-responsive consequentialist view of rational inquiry, which holds that inquiry is rational when it promotes the most value in response to reasons grounded in an agent’s total evidence. The article argues against the existence of distinct epistemic norms of inquiry and uses this view to explain and vindicate many observed deviations from classical rationality norms, proposing a nuanced relationship between bounded rationality and the Standard Picture. Finally, it situates this procedural turn in rationality within broader philosophical debates, including the zetetic turn in epistemology, emphasizing inquiry over static attitudes.